The UN Human Rights Council. - Ramcharan, Bertrand G. (Global institutions series., 2011)
The UN Human Rights Council provides a detailed insight into this important organization. The UN was founded in the hope that lasting peace would be built on the foundations of human rights and economic and social progress. In 2006 the Commission on Human Rights was replaced by the Human Rights Council as the principal UN body concerned with human rights. It is even possible that the council might eventually become a principal organ of the world organization. The Human Rights Council is already the subject of major public interest and controversy. The Council has been criticized for having dro.